Multi-detector Computed Tomography Evaluation of Renal Masses with Histopathological Correlation (MedS Alliance Journal of Medicine and Medical Sciences, 2024)
Introduction: The highest burden of renal cancer is seen in developed countries. As more countries adopt western lifestyle, incidence of renal cancer is predicted to increase in the future. Kidney cancer (KC) is estimated to cause 400 000 new cases worldwide each year, and it kills over 175 000 people worldwide each year.Materials and Methods: A prospective hospital-based study was carried out on 64 patients of various ages with clinically suspected renal masses at the Radiodiagnois department of the National Academy of Medical Sciences, Bir Hospital, and Kanti Children Hospitals Kathmandu. The Department of Pathology performed pre- and postoperative histopathology examinations on all patients with renal masses identified by Multi-detected Computed Tomography (MDCT). The histological results and diagnosis were then compared with the MDCT results and diagnosis in the pre-made proforma.Results: The results of the MDCT showed that 82.8 percent of the cases had malignant renal masses, while only 17.2 percent had benign renal masses. The results of the histopathological analysis also revealed malignant renal masses in over three-quarters (79.70%) of the cases, while only 20.30 percent had benign renal masses. More than half of the cases were male participants. 96.2%, 100%, 100%, 84.6%, and 96.8% were the sensitivity, specificity, PPV, NPV, and accuracy of MDCT for malignant masses renal, respectively. In the case of benign renal mass, the MDCT's sensitivity, specificity, PPV, NPV, and accuracy were 84.6%, 100%, 100%, 96.2%, and 96.8%, correspondingly.Conclusion: MDCT showed excellent sensitivity and specificity for both benign and malignant kidney cancers. Thus, we came to the conclusion that MDCT is helpful in assessing renal mass and distinguishing between benign and malignant masses.